Compatible paraffin@SiO2 microcapsules/polydimethylsiloxane composites with heat storage capacity and enhanced thermal conductivity for thermal management. (8th February 2022) - Zhou, Yuechen; Li, Shushan; Zhao, Yu; Ling, Ziye; Zhang, Zhengguo; Fang, Xiaoming
Abstract: Integrating phase change materials (PCMs) with polymers is expected to develop novel polymeric composites with heat storage capacity, thus showing potential applications in thermal management. Microencapsulation of solid-liquid PCMs by organic or inorganic shells can effectively prevent liquid leakage from the PCMs, thereby improving their application performance. Herein, phase change microcapsules with SiO2 shell were combined with polydimethylsiloxane (PDMS) to construct a novel kind of polymeric composite. It is shown that an interfacial interaction between the paraffin@SiO2 microcapsules and the PDMS occurs, which endows the two components with good compatibility. The paraffin@SiO2 microcapsules/PDMS composites exhibit slightly higher phase change temperatures than those of the microcapsules. The mass fraction of the microcapsules in the PDMS-based composites can reach 38.89 wt%, at which a latent heat value of 60.61 J/g is achieved, together with an enhancement by 80.71% in thermal conductivity as compared to that of pure PDMS. When the paraffin@SiO2 microcapsules/PDMS composite was employed for chip thermal management, the chip temperature reduced by 15.87%, compared with that using the one without any phase change microcapsules. It is revealed that the paraffin@SiO2 microcapsules/PDMS composites possess good thermal reliability. These merits make the paraffin@SiO2 microcapsules/PDMS composites show great promise in practical applications. Graphical abstract: Image 1